Persepsi Orang Tua terhadap Pembelajaran Calistung Anak Usia 4-5 Tahun - sofia, ari; Yulistia, Annisa; Nur Widayati, Putri (Jambura Early Childhood Education Journal, 2023)
This study aims to determine the parents' perception of learning to read and write arithmetic for children aged 4-5 years. The research method used in this research is descriptive quantitative. The population in this study was 314 parents and the sample in this study was 84 parents who sent their children to kindergarten in Labuhan Ratu sub-district. The sampling technique used in this research is Cluster Random Sampling. The data collection method used in this study was a closed questionnaire. Data were analyzed using interval formulas and percentage formulas. Based on the results of the study, parents' perceptions of learning calistung got a percentage score of 19.05% in the Strongly agree category, a percentage score of 26.20% in the Agree category, a percentage score of 48.80% in the Disagree category and for a percentage score of 5.95. % is in the category of Strongly Disagree. The results showed that most of the parents' perceptions of learning calistung for children aged 4-5 years did not agree, seen from the disapproving category, getting high results of 48 percent.